Subjective well-being of Filipino women who experienced intimate partner violence: A person-centered analysis - Bernardo, Allan Benedict I. (Animo Repository, 2017)
The study inquired into characteristics associated with the subjective well-being of Filipino women who had experienced intimate partner violence (IPV). Using a person-centered analysis, three groups of Filipino women who had experienced IPV were identified in terms of their reported levels of subjective well-being (high, moderate, low). The three groups were compared in terms of several relationship characteristics and also personal internal qualities. Results indicated that the women in the high and moderate subjective well-being groups were more likely to have left their abusive relationship and to report higher levels of optimism, self-esteem, and behavioral intentions that reflected self-mastery. Women in the low-wellbeing group were more likely to still be in their abusive relationship and report lower positive personal resources. The results are discussed in terms of how internal resources might allow women to deal with varied types of experiences in their abusive relationship. Implications for screening and counseling of abused Filipino women are discussed. © 2017, Springer Science+Business Media, LLC.